LATE CENOZOIC DENUDATION BY LARGE-MAGNITUDE LANDSLIDES IN THE EASTERN EDGE OF TIBETAN PLATEAU - Meng Q.R.; Wang E.; Qu H.J.; Hu J.M. (My University, 2006)
Eastern edge of the Tibetan Plateau is marked by the Longmen Shan, which experienced pronounced denudation in late Cenozoic and was previously attributed to river erosion. Our recent work, however, demonstrated that the landsliding must have played an important integral role in the surface processes. Various-scale landslides are present in the peripheral zone of the southern Longmen Shan, which were interpreted as overthrust-related klippen in previous works. We revisited these exotic blocks, and demonstrated that they were actually gravity-driven landslides in origin. The landslides are composed mostly of thick-bedded marine limestone and sandstone of Paleozoic-Early Triassic ages, and were detached along some weak zones like Lower Silurian phyllite and unconformities. Three types of landslides can be categorized, distributed, stacked, and coherent, and their differential occurrence is considered to bear upon both uplift rates of the Longmen Shan and foreland topography. Outward flow of lower-crustal materials from the Tibetan Plateau interior provides a feasible mechanism for initiating the uplift of its eastern flank in Cenozoic. Positive feedbacks are believed to have existed between extrusion of lower-crustal channel flow and surface denudation processes. Rapid denudation by large-magnitude landslides in conjunction with coeval river erosion in the southern Longmen Shan might have led to predominant sub-vertical extrusion of lower-crustal flow channel, as evidenced by nearly symmetric exhumation of the Pengguan massif. The northern Longmen Shan was comparatively less denuded, with few basement rocks cropping out, and landslides are absent in its front as well. Differential denudation between the southern and northern Longmen Shan might have in large part resulted from the lower-crustal flow that presumably moved to the southeast and had less impact on the northern Longmen Shan. © 2005 Elsevier B.V. All rights reserved.
Keywords: CENOZOIC; DENUDATION; LANDSLIDE; LONGMEN SHAN; TIBETAN PLATEAU